Water Management Practices Affect Arsenic and Cadmium Accumulation in Rice Grains - Liming Sun; Manman Zheng; Hongyan Liu; Shaobing Peng; Jianliang Huang; Kehui Cui; Lixiao Nie (The Scientific World Journal)
Cadmium (Cd) and arsenic (As) accumulation in rice grains is a great threat to its productivity, grain quality, and thus human health. Pot and field studies were carried out to unravel the effect of different water management practices (aerobic, aerobic-flooded, and flooded) on Cd and As accumulation in rice grains of two different varieties. In pot experiment, Cd or As was also added into the soil as treatment. Pots without Cd or As addition were maintained as control. Results indicated that water management practices significantly influenced the Cd and As concentration in rice grains and aerobic cultivation of rice furnished less As concentration in its grains. Nonetheless, Cd concentration in this treatment was higher than the grains of flooded rice. Likewise, in field study, aerobic and flooded rice cultivation recorded higher Cd and As concentration, respectively. However, growing of rice in aerobic-flooded conditions decreased the Cd concentration by 9.38 times on average basis as compared to aerobic rice. Furthermore, this treatment showed 28% less As concentration than that recorded in flooded rice cultivation. The results suggested that aerobic-flooded cultivation may be a promising strategy to reduce the Cd and As accumulations in rice grains simultaneously.